The Millennium Development Goals for Health : Rising to the Challenges. - Wagstaff, Adam (World Bank e-Library., 2004)
Annotation The report provides data on progress and trends in reaching the Millennium Development Goals for health, nutrition and population. It looks at poor-nonpoor disparities; health system reforms as a means of laying building blocks for the efficient and equitable delivery of interventions; the financing of health spending through domestic resources and aid; and improving the effectiveness of development assistance in health. In doing so, the report links the health Millennium Development Goal agenda with the broader poverty-reduction agenda. In addition, the report provides an inventory of World Bank activities related to the health Millennium Development Goals and other relevant activities as well as the activities of other multilateral and bilateral aid agencies. Non-health initiatives inside and outside the Bank of relevance, such as the Poverty Reduction Strategy Papers process, the Millennium Project; etc are also documented. Of interest to policymakers in developing countries as well as staff of development and technical agencies, this title provides a basis for the international community to further the Millennium Development Goal agenda in relation to health, nutrition and population.